COVID19 vaccination in adults with sickle cell disease is not associated with increases in rates of pain crisis - Elana Friedman; Caterina Minniti; Sean Campbell; Susanna Curtis (Hematology, 2022)
People with sickle cell disease (SCD) are more vulnerable to hospitalization, pneumonia, and pain following COVID-19 infection. However, given the association between the inflammatory response and vaso-occlusive crises in SCD and a case report of vaso-occlusive crises following administration of the ChAdOx1 nCov-195-7/AstraZeneca vaccine, there is concern that the administration of COVID-19 vaccines in people with SCD might provoke a vaso-occlusive crisis. To address this critical gap in knowledge, we sought to examine acute care usage for vaso-occlusive crisis and frequency and severity of side effects following COVID-19 vaccination among patients at the Montefiore Sickle Cell Center for Adults. As part of regular care, patients were asked if they had received COVID-19 vaccination and any side effects were noted. Electronic medical records were reviewed for the type of vaccine, dates received, episodes of vaso-occlusive crises within seven days of a dose, and side effects noted. The risk of average hospital utilization per week in 2019 was calculated as a baseline. We found that fewer than 1 in 10 patients presented to the hospital within seven days of vaccination and that the risk of hospital utilization was similar to the average risk in a week in 2019. Of patients who reported side effects, one reported a possible case of sensorineural hearing loss otherwise no other rare side effects, including thrombosis or death, were reported.